Narrative imagination in milieu therapy: Staff members' stories of relational change. Issue 4 (2nd October 2017) - Alsaker, Sissel; Ulfseth, Lena
ABSTRACT: Milieu therapy is an occupation-based treatment aimed at enhancing recovery in mental health patients that is grounded in the healing function of being and doing habitual and creative occupations together, thus transcending the individual. The purpose of this study was to explore these situated relations, discovering how relations emerge and are facilitated in the occupational context of a milieu therapy ward. The study is part of an ongoing ethnography published elsewhere. Narrative interviews with one occupational therapist, two nurses and a social worker were conducted on the ward. Data were interpreted through narrative analysis identifying occupation-based relational communication as the main finding. In particular, it was identified that the staff used narrative imagination to facilitate change in the way patients made meaning in the everydayness of milieu therapy. The findings present several relational encounters in which processes of narrative imagination hold significance for patients' mental health: Welcoming a devastated woman; Solving a mess together; From catastrophe to common ground, and Being at ease with one another. All findings are grounded in occupation-based relations, and the transformative potential of relational occupations is discussed in the milieu therapeutic context.